An epidemiological and clinical analysis of cutaneous drug eruption: A cohort of 164 patients - Cebeci, Dua; Yaşar, Şirin; Aytekin, Sema; Göktay, Fatih; Güneş, Pembegul (Journal of Surgery and Medicine, 2020)
Aim: Drug reactions are important and frequent complications of medical treatments. In this study we aimed to investigate the patients hospitalized with a diagnosis of cutaneous drug eruptions, implicated drugs, and related skin manifestations considering the literature. Methods: This retrospective cohort study was performed in Haydarpaşa Numune Training and Research Hospital, Dermatology and Venereology Department. The study comprised 164 patients that were diagnosed with cutaneous drug eruption between January 2010 and December 2016. Some parameters, such as demographic characteristics, type of the reaction, culprit drug groups, multiple drug usage, time between the onset of the drug intake and beginning of the eruption were recorded. Age, gender, symptoms, laboratory tests, diagnosis and treatment information were obtained through patient files. Causal relationship was assessed by Naranjo algorithm. Adverse drug reactions were categorized as definite, probable, possible, and absent. All values were expressed in percentages. The severity of the reaction caused by the drug was assessed with Hartwig’s Severity Assessment Scale. Results: Among 164 patients, there were 104 females and 60 males with a mean age of 46.3 (18.8) years. The most commonly encountered type of drug reactions were urticaria and angioedema (42.1 %), followed by morbilliform drug eruption (31.7%). More cutaneous reactions were noted with NSAIDs (18.9%), antibiotics (15.2%) and the combination of NSAIDs and antimicrobial agents (9.8%). Time between the onset of eruption and the intake of the drug varied by hours to months. Some of these patients also described similar reactions related to drugs in the past. Conclusion: Knowledge of these drug eruptions, the causative drugs and the prognostic factors is important for clinicians. It is recommended to advise patients to carry a list in their wallets indicating their drug allergies and/or intolerances, especially if they had a severe reaction before. We conclude that a careful follow-up should be performed with NSAIDs, antibiotics and anti-epileptics. The combination of drugs, including NSAIDs and antibiotics should be avoided as much as possible.